2004
DOI: 10.1007/s15010-004-3088-y
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking Influenza Virus Infection in Patients Attended to in the Emergency Department

Abstract: Influenza virus infection has a great and underestimated impact in the emergency department during influenza epidemics. High frequency of confusing symptoms, which overcome classical influenza syndrome in adult people with comorbidity, may explain this effect. Disproportionate prostration and cough are symptoms that independently predict its diagnosis in the global adult population, whereas in the elderly, fever and cough should arouse this suspicion whether or not they present classic symptoms. In our setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
2
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 33 publications
2
36
2
2
Order By: Relevance
“…In contrast to other studies, 8,16,18,23 this study found no effect of age on presentation. Cough alone had the highest sensitivity (91%), while fever had a sensitivity of 50%.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to other studies, 8,16,18,23 this study found no effect of age on presentation. Cough alone had the highest sensitivity (91%), while fever had a sensitivity of 50%.…”
Section: Discussioncontrasting
confidence: 99%
“…1 The clinical characteristics of influenza infection have been well described for outpatients, 2-7 emergency department patients, 8,9 and nursing home residents. 10 Several different case definitions have been proposed for influenza in those populations.…”
Section: Case-control Study Of Clinical Features Of Influenza In Hospmentioning
confidence: 99%
“…Many studies have described the clinical presentation of influenza in outpatient settings, 2-7 emergency departments, 8,9 and long-term care facilities. 6 Several meta-analyses have also addressed the clinical features of influenza in outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties of identifying influenza virus infection on the basis of clinical characteristics have been well described for outpatients, [2][3][4][5][6][7] patients in the emergency department, 8,9 and residents of nursing homes. 10 There are fewer recent data regarding the clinical presentation of hospitalized patients with influenza.…”
Section: Infect Control Hosp Epidemiolmentioning
confidence: 99%
“…The difficulties in identifying influenza virus infection on the basis of clinical characteristics have been well documented [5][6][7][8][9]. Several studies have shown that a high fever and cough represent best predictors for influenza infection in adults while influenza virus circulates in any given community [10][11][12].…”
Section: Introductionmentioning
confidence: 99%